2020
DOI: 10.1371/journal.pone.0239547
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium-protein complex inhibits human adipocyte differentiation through the activation of β-catenin and LKB1/AMPK signaling pathway

Abstract: Obesity is a common disease over the world and is tightly associated with diabetes mellitus, cardiovascular and cancer disease. Although our previous study showed that the synthetic vanadium-protein (V-P) complex had a better effect on antioxidant and antidiabetic, the relative molecular mechanisms are still entirely unknown. Hence, we investigated the effect of the synthetic V-P complex on adipocyte differentiation (adipogenesis) using human preadipocytes to clarify its molecular mechanisms of action. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…At the same time, our previous experimental [ 34 ] and human [ 28 ] studies demonstrated an inverse association between V levels and obesity. Correspondingly, V supplementation was shown to modulate adipogenesis [ 35 ], thus being indicative of its potential antiobesity effects [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, our previous experimental [ 34 ] and human [ 28 ] studies demonstrated an inverse association between V levels and obesity. Correspondingly, V supplementation was shown to modulate adipogenesis [ 35 ], thus being indicative of its potential antiobesity effects [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the studies by Zhang et al [ 49 ] showed that vanadium complexes with concentrations below 20 µg/mL have low cytotoxicity. During an excessive supply of nutrients, the growth of white adipose tissue (WAT) prevents ectopic fat accumulation by affecting the rate of differentiation to adipocytes in preadipocytes [ 50 ].…”
Section: Discussionmentioning
confidence: 96%
“…The γ isoform exists in all tissues, is predominantly expressed in adipose tissue, and is essential for the differentiation and function of adipocytes [ 27 , 28 ]. A previous study reported that PPARγ was the most highly expressed and necessary in adipocytes for differentiation and is regarded as a master regulator of adipogenesis and a key regulator of gene expression in matured adipocytes [ 29 , 30 , 31 ]. Besides these, recently, lots of experiments related to obesity in whole-body PPARα − deficient mice (PPARα −/− ) and in mice lacking PPARα only in hepatocytes (PPARα hep−/− ) were performed.…”
Section: Discussionmentioning
confidence: 99%